Additive manufacturing of highly dense anisotropic Nd–Fe–B bonded magnets. (1st July 2020) - Gandha, Kinjal; Nlebedim, Ikenna C.; Kunc, Vlastimil; Lara-Curzio, Edgar; Fredette, Robert; Paranthaman, M. Parans
Abstract: Extrusion based big area additive manufacturing process is utilized for fabrication of dense anisotropic bonded magnets. High loading fraction (≥70 vol%) of magnequench anisotropic Nd–Fe–B powder in nylon is used for preparing anisotropic bonded magnets. A higher energy product of ~143.2 kJ/m 3 is obtained for the post printed magnetic field aligned at 1 Tesla. These findings make an important step towards the fabrication of gap magnets with energy product between ferrite and Nd–Fe–B sintered magnets. Moreover, printed bonded magnets exhibited better thermal stability, mechanical properties and superior magnetic properties compared to commercial injection molded magnets. Graphical abstract: Development in energy product, BH max of additively manufactured anisotropic bonded NdFeB magnets using BAAM system. Image, graphical abstract